Opera de compvto: a tempore post Gerlandvm vsqve ad Iohannem de Sacrobosco - Lohr, Alfred (Corpvs Christianorvm, 2025)
"Given the importance of calendar calculations, it is not surprising that numerous contemporary texts comprehensively covered this subject. The current edition includes 15 texts from the period 1103 to 1232, 14 of which have not been printed before. Only the most successful of these texts, written by Johannes de Sacrobosco, was first printed in 1538 and subsequently in many other editions. The rich content of the texts published here is made accessible through several indexes, including an alphabetical subject index."--publisher's website